The effectiveness and cost-evaluation of manual therapy and physical therapy in patients with sub-acute and chronic non specific neck pain. Rationale and design of a Randomized Controlled Trial (RCT) - van Assen Luite (BMC Musculoskeletal Disorders, 2010)
Abstract Background Manual Therapy applied to patients with non specific neck pain has been investigated several times. In the Netherlands, manual therapy as applied according to the Utrecht School of Manual Therapy (MTU) has not been the subject of a randomized controlled trial. MTU differs in diagnoses and treatment from other forms of manual therapy. Methods/Design This is a single blind randomized controlled trial in patients with sub-acute and chronic non specific neck pain. Patients with neck complaints existing for two weeks (minimum) till one year (maximum) will participate in the trial. 180 participants will be recruited in thirteen primary health care centres in the Netherlands. The experimental group will be treated with MTU during a six week period. The control group will be treated with physical therapy (standard care, mainly active exercise therapy), also for a period of six weeks. Primary outcomes are Global Perceived Effect (GPE) and functional status (Neck Disability Index (NDI-DV)). Secondary outcomes are neck pain (Numeric Rating Scale (NRS)), Eurocol, costs and quality of life (SF36). Discussion This paper presents details on the rationale of MTU, design, methods and operational aspects of the trial. Trial registration ClinicalTrials.gov Identifier: NCT00713843